Seasonal Reproduction in the Male Black Bear Ursus Americanusc and Male Polar Bear Ursus Maritimus - Howell-Skalla, Lesley Ann (1999)
Both the black bear (Ursus americanus) and polar bear (Ursus maritimus) are long day seasonal breeders. Males undergo testicular regression during the non-mating season and testicular recrudescence during the pre-mating season. The present investigation was undertaken to begin to study the role of serum FSH, LH, and particularly PRL in testicular recrudescence in the male black bear. The specific objectives of this research were: (1) to determine if testicular LH-, FSH-, and PRL-receptor mRNA abundance changes during testicular recrudescence and is associated with changes in serum LH, FSH, PRL, and T and (2) to determine if suppression of the spring increase in serum PRL concentrations affects testicular recrudescence. The major findings were: (1) the abundance of testicular LH and PRL receptor mRNA changes seasonally during testicular recrudescence: both increased dramatically in March during mid-recrudescence, coincident with increased serum concentrations of PRL and T; and (2) the treatment of male bears with Parlodel LAR during testicular recrudescence prevented the spring increase in serum PRL concentrations and was associated with lower levels of testicular LHr and PRLr mRNA in March, suppressed serum T concentrations in March and April, and smaller testis size in May. Collectively, these data are consistent with the hypothesis that increasing serum PRL concentrations associated with lengthening day length may promote testicular recrudescence in the black bear by enhancing steroidogenesis. This thesis also provides new information on the reproductive biology of the male polar bear. There were three major findings: (1) testicular size is positively correlated with breeding season and serum T concentrations; (2) serum LH is only detectable during the breeding season in April, coincident with peak serum concentrations of T; and (3) serum PRL concentrations are positively correlated with day length. Both of these studies contribute novel information to the field of bear reproductive biology and can be used to ...